Pengaruh motif IPO dan total aset emiten terhadap herding behavior pada pasar modal Indonesia - Rohmad Fuad Armansyah (Journal of Business & Banking, 2015)
IPO (Initial Public Offerings) is one of financing alternatives for the company. In this way the company can get some funds for corporate purposes, but problems arise when they are going public. The problem deals with under pricing or overpricing. This study tries to lift and apply the concept of the IPO as done previously to develop alternative focusing on motive IPOs and total assets of issuers on the phenomenon of herding on a sample of 320 companies conducting an IPO in 1995-2014 in the Indonesia Stock Exchange. Sample was taken by using purposive sampling with criteria not entirely de-lists from the stock exchange. The data were analyzed using multiple regression analysis and path analysis to examine the relationship between motives IPO, the total assets of the issuer, to herding. The result shows that the motive IPO has positive effect on herding and has an indirect negative effect but it is not statistically significant. Total assets of the issuer have a positive influence and statistically significant towards herding during the first day of trading on the stock exchange. The implications of this research, investors in the primary market should consider the information on the total assets of the company in making investment decisions and they do not lead to herding behavior that can harm the investment market.